Implementasi Program Petani Mandiri dalam Meningkatkan Kesejahteraan Petani di Kecamatan Sumberrejo Kabupaten Bojonegoro - Reny July Rivany; Ananta Prathama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the implementation of the Independent Farmer Program in Sumberrejo Sub-district, Bojonegoro Regency, a flagship priority program of the local government. This program is governed by Regent Regulation Number 43 of 2020 concerning the Second Amendment to Regent Regulation Number 20 of 2019, which amends Regent Regulation Number 48 of 2018 on the Independent Farmer Program. The program seeks to improve farmers' welfare through empowerment and access to agricultural resources. The study's findings indicate that the program faces challenges, such as low farmer awareness and the suboptimal implementation of several initiatives. The research employs a qualitative approach with a case study method, involving in-depth interviews, field observations, and document analysis. Recommendations include enhancing farmer outreach and training, as well as strengthening program monitoring and evaluation to ensure effectiveness and sustainability.